AN INTERESTING CASE OF CMV RETINITIS IN A PATIENT OF ALL ON MAINTENANCE THERAPY - PAWAN KUMAR SINGH; Manoranjan Mahapatra; TULIKA SETH; Pravas Chandra Mishra; Pradeep Venkatesh; Vineet Sehgal (Mediterranean Journal of Hematology and Infectious Diseases, 2014)
A 45 years old male, known case of T-cell Acute Lymphoblastic Leukemia on maintenance therapy presented with painless progressive diminution of vision in both eyes. Evaluation revealed Cytomegalovirus Retinitis with low CD4 counts. CMV retinitis is usually seen in HIV disease or in post allogenic stem cell transplant recipient patients. CMV retinitis occurring in ALL maintenance phase is very rare. The patient showed some improvement with intra-vitreal and intra-venous Gancyclovir injections.